THE pH AND TEMPERATURA EFFECTS IN STABILIZATION PONDS AT A UNIVERSITY CAMPUS - Guzmán Pérez, Jennifer; Cruz Hernández, Citlali Vianey; Torres Castro, Pamela; Domínguez Rodríguez, Verónica Isidra; Adams Schroeder, Randy Howard; Baltierra Trejo, Eduardo; Gómez Cruz, Rodolfo (Kuxulkab', 2022)
Stabilization ponds are complex biochemical reactors and represent one of the most viable alternatives for wastewater treatment in university campuses, as they require low cost of operation, low maintenance, and can be used as educational biomaterial. The treatment quality of 106,020 m3/day of wastewater was monitored in situ by means of temperature and pH, at three hours and different depths, in the campus stabilization system of the División Académica de Ciencias Biológicas (DACBiol), from the Universidad Juárez Autónoma de Tabasco (UJAT), for 30 days, in the months of October and November 2019. Due to the maximum temperatures recorded of 28 °C and 26 °C in the affluent and effluent, respectively, and the maximum pH of 7.4 obtained in the anaerobic-facultative lagoon, tending to be slightly acidic in the morning, this stabilization system requires maintenance to improve its effectiveness.
Keywords: Sewage water; Monitoring; in situ; Affluent; Effluent